Landscape-scale endophytic community analyses in replicated grapevine stands reveal that dieback disease is unlikely to be caused by specific fungal communities - Monod, Vinciane; Hofstetter, Valérie; Viret, Olivier; Zufferey, Vivian; Gindro, Katia; Croll, Daniel (American Society for Microbiology, 2025)
Tree diebacks are complex and multifactorial diseases with suspected biotic and abiotic components. Microbiome effects on plant health are challenging to assess due to the complexity of fungal and bacterial communities. Grapevine wood dieback is the main threat to sustainable production worldwide, and no causality with microbial species has been established despite long-standing claims of fungal drivers. Here, we aimed to test the hypothesis that grapevine esca disease progression has reproducible drivers in the fungal species community. For this, we analyzed a set of 21 vineyards planted simultaneously with a single susceptible cultivar to provide unprecedented replication at the landscape scale. We sampled a total of 496 plants at the graft union across vineyards in 2 different years to perform deep amplicon sequencing analyses of the fungal communities inhabiting grapevine trunks. The communities were highly diverse with a total of 4,129 amplified sequence variants assigned to 697 distinct species. We detected trunk fungal community shifts over years of sampling, vineyards and climatic conditions, as well as disease status. However, we detect no specific fungal species driving symptom development across vineyards, contrary to long-standing expectations. The high degree of environmental standardization in the decade-long experimental plots and the well-powered replication provide the clearest evidence yet that grapevine wood dieback is most likely caused by environmental factors rather than specific pathogens. Furthermore, our study shows how landscape-scale replicated field surveys allow for powerful hypothesis testing for complex dieback disease drivers and prioritize future research directions.